Pembuatan Aplikasi Monitoring Karantina Mandiri Orang dalam Pengawasan (ODP) COVID-19 di Kota Depok - Risna Sari; Mera Kartika Delima Yanti; Dewi Yanti Liliana; Iklima Ermis Ismail (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The COVID-19 pandemic that has hit all countries in the world is a sudden humanitarian disaster. This virus is highly contagious, so it is necessary to make direct contact to prevent widespread transmission. Meanwhile, for people who have had contact with people with COVID-19, it is necessary to carry out tracing and activity activities so as not to cause more people to be exposed to COVID-19. Therefore, a supporting infrastructure is needed in the form of web and mobile-based applications to monitor self-quarantine for COVID-19 People Under Supervision (ODP). The Informatics Engineering Study Program, Department of Informatics and Computer Engineering, Jakarta State Polytechnic developed a web-based and mobile-based software application made for the Depok Jaya Community Health Center to support ODP COVID-19. ODP can report complaints and grievances through the mobile application, while the Depok Jaya Community Health Center conducts monitoring through a web-based application. By using this application, it is hoped that it can break the chain of spreading COVID-19 in Depok City, especially in Depok Jaya District.DOI: https://doi.org/10.26905/abdimas.v6i2.5090